قرض الإيجار كإستراتيجية حديثة للتمويـل - دراسة مقارنة بين الجزائر والمغرب - - بوراس, أحمد; طلحي, سماح (Sciences humaines; Vol. 35 (2014): SCIENCES HUMAINES)
تتناول هذه الورقة موضوع قرض الإيجار كبديل أمثل وفعال لتمويل المؤسسات الاقتصادية، فرغم تعدد مصادر التمويل يبقى من الضروري الاهتمام بالتقنيات التمويلية الحديثة والتي من بينها قرض الإيجار الذي أثبت نجاعته في أغلب البلدان المتقدمة، وذلك من خلال إدراك المفاهيم الأساسية المتعلقة بهذه التقنية وأهميتها كبديل تمويلي فعال، مع الإشارة إلى واقع هذا النوع من التمويل في كل من الجزائر والمغرب     This study deals with leasing as one of the more appropriate entreprise’s financing means. Despite the availability of many financing sources, it is imperative to take into account the modern financing techniques such as leasing. This later is a mean of financing which has proved its efficiency in financing enterprises in advanced countries. Therefore the highlights on the comprehension of the basic concepts of leasing and its importance as an efficient financing alternative is necessary. It also emphasis on the Algeria and the Morocco cases.